A serum factor that activates the phosphatidylinositol phosphate signaling system in Xenopus oocytes. - Tigyi, G (1990)
Blood sera from many vertebrate species elicit large oscillatory chloride currents in oocytes from the frog Xenopus laevis. Rabbit serum was active at dilutions as great as one part in 10 million. Intracellularly applied serum was ineffective, and externally applied serum failed to trigger oscillatory currents when the intracellular level of ionized calcium was prevented from rising by loading the oocyte with EGTA. The serum also caused an increase of inositol 1,4,5-trisphosphate in the oocyte. We conclude that serum contains a factor which activates a membrane receptor that is coupled to the phosphatidylinositol second messenger system. The active factor is a protein with an apparent molecular mass of 60-70 kDa in gel permeation chromatography. Although the normal function of the serum factor is still unknown, it may have far-reaching implications, because it acts on the multifunctional phosphatidylinositol phosphate signaling system. Also, because of its great potency the serum factor and Xenopus oocytes are very useful for probing the operation of the phosphatidylinositol system.